2019
DOI: 10.3847/1538-4357/ab4a0f
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton RGS Spectroscopy of the M31 Bulge. I. Evidence for a Past AGN Half a Million Years Ago

Abstract: Existing analysis based on spectra from the Reflection Grating Spectrometer (RGS) onboard XMM-Newton already shows that the G-ratio of the O vii Heα triplet in the inner bulge of M31 is too high to be consistent with a pure optically thin thermal plasma in collisional ionization equilibrium (CIE). Different processes that may affect properties of diffuse hot plasma were proposed, such as resonance scattering (RS) and charge exchange (CX) with cold gas. To determine which physical process(es) may be responsible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Finally, in addition to the star formation rate, a central AGN could also have an impact on the surrounding CGM. Zhang et al (2019) found, using X-ray spectroscopy, a possible evidence in M31 for a past AGN event that happened half a million years ago. In this very short timescale, even if the clouds were ejected at 2000 km s −1 they would reach a distance of about 1 kpc from the centre, much smaller than the distances that we are probing in this study.…”
Section: Outflowmentioning
confidence: 98%
“…Finally, in addition to the star formation rate, a central AGN could also have an impact on the surrounding CGM. Zhang et al (2019) found, using X-ray spectroscopy, a possible evidence in M31 for a past AGN event that happened half a million years ago. In this very short timescale, even if the clouds were ejected at 2000 km s −1 they would reach a distance of about 1 kpc from the centre, much smaller than the distances that we are probing in this study.…”
Section: Outflowmentioning
confidence: 98%
“…This question is given additional relevance by the compelling evidence that now exists for recent (Myr-timescale) activity at the GC, including the giant γ-ray emitting Fermi Bubbles (Su et al 2010;Dobler et al 2010;Ackermann et al 2014), their counterparts in X-rays (Bland-Hawthorn & Cohen 2003;Miller & Bregman 2016), microwaves (Finkbeiner 2004), and polarized radio emission (Carretti et al 2013), the presence of smaller-scale (≈400 pc) radio lobes within the Bubbles (Heywood et al 2019), and the tentative detection of radio jets (Su & Finkbeiner 2012), though see Ackermann et al (2014). Furthermore, AGN activity on ∼Myr timescales has recently been inferred from X-ray studies of M31 (Zhang et al 2019), suggesting that such processes are common in MW-mass spiral galaxies. Our UV kinematic analysis of the Magellanic Stream brings a new method for gauging the GC activity: assessing its impact on the extended gaseous environment.…”
Section: Introductionmentioning
confidence: 94%
“…The RGS spectra provide us spatial information of extended emission over 5 arcmin width along the cross-dispersion direction when the X-ray peak of the target locates near the pointing position (e.g., Chen et al 2018;Zhang et al 2019). Thus, we used only two datasets in 2002 and 2007 which have quite smaller offsets than the others (see Table 1).…”
Section: Rgsmentioning
confidence: 99%